Effectiveness of Alteplase in Management of Prosthetic Valve Thrombosis in High Risk Surgical Cases - Ghous, Muhammad Waleed; Nadeem, Asif; Shah, Syed Akmal; Abbas, Ali; Khan, Muhammad Babar; Ateeq , Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the effectiveness of alteplase in patients presented with prosthetic valve thrombosisStudy Design: Analytical Cross-Sectional studyPlace and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan from Jan-Sep 2024.Methodology: Patients aged 18-75years regardless of gender with left-sided mechanical prosthetic valve thrombosis who were deemed high-risk or unfit for surgery were included. Diagnosis was confirmed using transthoracic echocardiography and fluoroscopy. Patients received an accelerated dose of 50mg Alteplase intravenously over 2-hours. Follow-up evaluation included 2D-echocardiography and fluoroscopy 4-hours post-treatment to assess valve function and mobility.Results: Twenty-two patients [males: 11(50.0%), females:11(50.0%)], with mean age 36.73±14.58years were included in the study. All patients were in NYHA class III-IV and hemodynamically unstable. Fourteen (63.6%) patients experienced Atrial Fibrillation, and 11(50.0%) had suboptimal INR, on admission. Cine-fluoroscopy revealed completely stuck valve in 15(68.2%) patients and mitral valve involved in 17(77.3%) patients. Alteplase showed complete and partial response in 14(63.6%) and 4(18.2%) patients respectively, with overall clinical improvement in 18(81.8%) patients. Patients under 40 years and males showed higher response rate (64.3%) to treatment (p>0.05). Minor bleeding occurred in 3(13.6%) patients, while no major bleeding, stroke, or hematoma was reported.Conclusion: Alteplase, administered as an accelerated dose of 50mg over 2-hours, is an effective and safe treatment for obstructive prosthetic valve thrombosis in patients at high risk for surgery. With a high rate of clinical improvement and minimal complications, this regimen presents a viable first-line treatment for PVT.